A study on factors that influence consumer intention to purchase counterfeit product in UiTM Bandaraya Melaka / Siti Nur Fatin Ayunie Che Mohd Rosli - Che Mohd Rosli, Siti Nur Fatin Ayunie (Faculty of Business and Management, 2018)
This study is intends to investigate the factors that influence consumer intention to purchase counterfeit product among students in UiTM Bandaraya Melaka. Four objectives have been determined in this study. First, to identify whether there is significant relationship between social influence and consumer intention to purchase counterfeit products. Second, to identify whether there is significant relationship between pricing and consumer intention to purchase counterfeit products. Third, to identify whether there is significant relationship between quality preference and consumer intention to purchase counterfeit products. Lastly, to identify which factors gives most influence on consumer intention to purchase counterfeit products. The population of the study consist of 1711 students of UiTM Bandaraya Melaka and the data were collected by distributing 320 questionnaires but only 313 respondents returned the questionnaires. Therefore, only 313 questionnaires were used in this study. To analyse the data, descriptive, correlation, and regression analysis were used. From the correlation analysis conducted, the result revealed that there are significant positive relationship between all the independent variables (social influence, pricing and quality preference) and the dependent variables (consumer intention to purchase counterfeit product). Meanwhile, from the regression analysis conducted, it was found that quality preference gave more influence to consumer intention to purchase counterfeit product.